Blockchain Technology Consensus Algorithms and Applications: A Survey - Alsaqqa, Samar; Almajali, Sufyan (International Journal of Interactive Mobile Technologies (iJIM), 2020)
One of the new promising technologies for the future is blockchain. It has become one of the popular techniques for various transactions and applications in many different areas such as economy, business, and government. Blockchain technology started with cryptocurrency and bitcoin applications for a safe and transparent environment. Blockchain is a hybrid technology that incorporates various technologies and tools such as mathematics, peer-peer networking, cryptography algorithms, and consensus algorithms. This survey highlights the latest studies in blockchain and consensus algorithms. The study covers the most recent blockchain applications in various domains and sectors. Furthermore, the study gives an insight into the latest adoption of the blockchain in the real world.